DOES THE VALUE OF COAL MINING COMPANIES IN INDONESIA AFFECT GREEN ACCOUNTING, CSR, AND PROFITABILITY? - Murdiansyah, Isnan -; Khairunnisa, Desi Pratiwi Adhila; Siswanto, Siswanto; Yuliana, Indah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The focus of this research is to find out whether profitability, CSR, and green accounting affect firm value. Coal mining companies listed on the IDX are the object of research, and the sampling is purposive sampling. The data is taken from the IDX website and related companies. The data collected includes environmental cost components, CSR index, ROE, and Tobins'q. Data analysis was performed using linear regression analysis. The results of the study show that although the application of green accounting and CSR has no effect on firm value, profitability as measured by ROE has an effect on firm value. But overall, the application of green accounting, CSR, and profitability affect the value of the company.